The Global Course of the Information Revolution Recurring Themes and Regional Variations - Hundley, Richard (RAND Corporation, 2003)
Advances in information technology are heavily influencing ways in which business, society, and government work and function throughout the globe, bringing many changes to everyday life, in a process commonly termed the "information revolution." This book paints a picture of the state of the information revolution today and how it will likely progress in the near- to mid-term future (10 to 15 years), focusing separately on different regions of the world-North America, Europe, the Asia-Pacific region, Latin America, the Middle East and North Africa, and sub-Saharan Africa.